2021
DOI: 10.1111/acel.13445
|View full text |Cite
|
Sign up to set email alerts
|

Telomere length and metabolic syndrome traits: A Mendelian randomisation study

Abstract: Observational studies have revealed associations between short leucocyte telomere length (LTL), a TL marker in somatic tissues and multiple Metabolic Syndrome (MetS) traits. Animal studies have supported these findings by showing that increased telomere attrition leads to adipose tissue dysfunction and insulin resistance. We investigated the associations between genetically instrumented LTL and MetS traits using Mendelian Randomisation (MR). Fifty‐two independent variants identified at FDR<0.05 from a genome‐w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 62 publications
2
22
0
Order By: Relevance
“…Mendelian randomization (MR) is an epidemiological tool using data from genetic studies to estimate the nonconfounded associations between exposures and outcomes. We and others have recently explored the relationships between LTL and MetS traits using MR but failed to detect any causal associations between short telomeres and higher risk of MetS or its constituent traits [11, 20]. On the contrary, longer LTL was associated with higher blood pressure (BP), higher waist‐hip ratio adjusted for body mass index (WHRadjBMI), and increased MetS risk [20].…”
Section: Introductionmentioning
confidence: 99%
“…Mendelian randomization (MR) is an epidemiological tool using data from genetic studies to estimate the nonconfounded associations between exposures and outcomes. We and others have recently explored the relationships between LTL and MetS traits using MR but failed to detect any causal associations between short telomeres and higher risk of MetS or its constituent traits [11, 20]. On the contrary, longer LTL was associated with higher blood pressure (BP), higher waist‐hip ratio adjusted for body mass index (WHRadjBMI), and increased MetS risk [20].…”
Section: Introductionmentioning
confidence: 99%
“…Previously reported meta-analysis of GWAS data from participants of European ancestry identified 52 potential SNPs for this evaluation. Our data validation reduced this to 16 SNPs related to TL, which were also independent of any potential confounding factors and then applied as instrumental variables in our MR evaluations to identify any causal relationships between TL and HL [ 29 , 34 , 35 ]. The proportion of variance in average TL explained by individual SNPs ranged from 0.08% to 0.36% [ 35 ], and the F statistic of these SNPs was much greater than 10, indicating that the possibility of weak instrumental variable deviation was low.…”
Section: Resultsmentioning
confidence: 99%
“…A recent report indicated that telomere shortening is not believed to be directly involved in other signs of aging but only a regulator of the genetic changes in human gene expression associated with cellular aging, with the majority of the genes affected by TL involved in apoptosis and cell death [ 12 ]. Similarly, there have been several observational studies that have suggested a potential link between TL and various cancers and non-neoplastic diseases, but none of these reported any causality when evaluated by MR, with these outcomes likely the result of the sensitivity of observational studies to confounding effects and reverse causality [ 29 , 34 , 42 , 43 ]. At present, there is insufficient evidence to suggest that TL is the driving etiological factor in many diseases, and the pathogenic link between TL and HL needs to be evaluated in greater detail.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unexceptionally, another MR study including 78 592 Europeans suggested that genetically instrumented longer LTL was associated with raised SBP and DBP, while no unbalanced horizontal pleiotropy was detected 51 . A possible explanation for this stems from an epidemiological study in the Framingham Offspring Cohort that longer LTL was associated with increased aldosterone-to-renin ratio and eventually causes hypertension 52 .…”
Section: Discussionmentioning
confidence: 99%